The effect of locally-generated revenue, capital expenditure, and investment on economic growth in Lamongan (Indonesia), 2010–2019 - Inayati, Fitri Nur; Soesatyo, Yoyok; Witjaksono, Andre Dwijanto (Technology audit and production reserves, 2020)
Since economic growth is a macro indicator of successful development, all countries strive to get maximum economic growth to create public welfare, especially for developing countries. Therefore, using the example of a city in one such country, namely Lamongan in Indonesia, let’s examine the effects of local income, capital expenditure and partial investment simultaneously on economic growth. Thus, the object of the research is the influence of locally-generated revenue, capital expenditure, partial investment, and simultaneously economic growth in the Lamongan in 2010–2019. This research was established with a quantitative approach. The data used are secondary data published by the Central Bureau of Statistics of Lamongan, the Regional Financial and Asset Management Agency of Lamongan, the Office of investment, and One-Stop Services, Lamongan in 2010–2019. The results of the study conclude that partially the locally-generated revenue variable has a significant negative effect on economic growth in Lamongan in 2010–2019, capital expenditure has a significant positive impact on economic growth in Lamongan in 2010–2019, and investment did not hurt economic growth in Lamongan in 2010–2019. Simultaneously, the locally-generated revenue variables, capital expenditure, and acquisition significantly affected Economic Growth in Lamongan in 2010–2019. This study’s results are expected to become information, reference materials, and references to develop and expand future research. For the Lamongan government, this research can be used as a necessary consideration and input to improve policies related to increasing economic growth of country.